The Sources and Authorship of The Coppy of a Letter of Father Philips (1641). (10th March 2018) - Schneider, Gary
Abstract: Since 1641, the principal letter in the pamphlet The Coppy of a Letter of Father Philips has been attributed to Robert Philip, confessor to Queen Henrietta Maria. This article demonstrates that this almost 400-year-old attribution is incorrect and that Philip did not in fact write the letter, but rather that the letter is an amalgamation of three different intercepted letters read in Parliament during June 1641. Evidence is also presented that at least one of the three letters in question was written by secular priest George Leyburn and was intended for Richard Smith, bishop of Chalcedon.